Inside-out : pathogenesis of enterococcal-associated wound infections - Tay, Wei Hong (2018)
Wound infections represent a significant health problem, due to their difficulty in management and the cost associated with their treatment. Surgical wounds are often infected with Enterococci, which is one of the top 3 most frequently isolated bacterial species from this site. However, mechanisms that govern and contribute to Enterococcal pathogenesis in wounds have not been elucidated. The following thesis hypothesized that polymicrobial wounds with Enterococci will result in a poorer disease outcome, due to synergistic effects with other microbial species. We also proposed that persistent and recurring wound infections are due to Enterococci having a dual extracellular and intracellular lifestyle. We used an unbiased screening approach mimicking in vivo wound conditions to screen for Enterococcal factors that are responsible for enhanced E. coli biofilm growth in wounds. We demonstrated that the Enterococcal metabolite, L-ornithine can induce siderophore production in E. coli, resulting in enhanced virulence under iron limiting conditions. Using both in vitro and in vivo models, we also showed that Enterococci have a dual extracellular and intracellular infective lifestyle. Together, these studies demonstrate the contributions of Enterococci in wound infections, both outside of the host cells and inside of the host cells. Our work provides evidence of cooperative extracellular interactions between Enterococci and other co-infecting microbial species in wounds, and demonstrates that it has a dual infective lifestyle. Our findings will be useful to clinicians in managing persistent wound infections and could potentially result in the development of improved treatment strategies or therapeutics.